2010
DOI: 10.1007/978-3-642-15745-5_24
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Emphysema Progression

Abstract: Emphysema is one of the most widespread diseases in subjects with smoking history. The gold standard method for estimating the severity of emphysema is a lung function test, such as forced expiratory volume in first second (FEV1). However, several clinical studies showed that chest CT scans offer more sensitive estimates of emphysema progression. The standard CT densitometric score of emphysema is the relative area of voxels below a threshold (RA). The RA score is a global measurement and reflects the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To date, groups who evaluate the prognostic value of registered data sets typically use statistically based metrics, such as the mean of the Jacobian, differences in HU or dissimilarity measures based on the histograms of the CT images where information from the measure is pooled throughout the lung into a single outcome measure which forfeits the spatial information that is inherent in the CT images 9,10,14,27 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, groups who evaluate the prognostic value of registered data sets typically use statistically based metrics, such as the mean of the Jacobian, differences in HU or dissimilarity measures based on the histograms of the CT images where information from the measure is pooled throughout the lung into a single outcome measure which forfeits the spatial information that is inherent in the CT images 9,10,14,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Image registration can be employed to match inspiratory scans obtained serially to assess emphysema progression (45,46). Gorbunova and colleagues (47) used image registration in a small study of 27 patients with severe emphysema to match serially acquired images at baseline, and at 3, 12, 21, and 24-30 months, and found that measurement of local disease progression could be consistently demonstrated. Image registration-based algorithms have been proposed for the measurement of local progression of emphysema that is minimally affected by changes in lung volume between baseline and follow-up (48,49).…”
Section: Emphysemamentioning
confidence: 99%
“…This compared corresponding regions of interest between baseline and follow-up CT scans, instead of direct voxel-to-voxel density comparison. 75 Histogram-based features were obtained from random samples of corresponding regions in the lung and were compared using L1-norm and Kullback–Leibler divergence dissimilarity indices. The use of image matching for disease progression is heavily reliant on the comparison of CT densities between corresponding locations of baseline and follow-up scans.…”
Section: Applications In Copdmentioning
confidence: 99%